The Implementation of Entrepreneurship Course in EFL Classroom Indonesian Higher Education Context - Mahmud, Adi F; Idul, Muhammad; Noni, Nurdin (EDUKASI, 2024)
The research aims to investigate the students' perspectives, benefits, and challenges throughout the delivery of the entrepreneurship course. A qualitative approach employing a descriptive design. It was carried out English education master's program at UNM. A total of thirteen English students from the academic years 2022-2023 and 2023-2024 as respondents. Data gathered through document analysis, questionnaires, and in-depth interviews. Data examines first, questionnaire analysis using Likert scales. Both the document and the in-depth interviews ware analysed outlined by Gay et al. (2009), which involves reading/memorising, describing, and classifying. The results indicate that the entrepreneurship programme at UNM is of exceptional quality, characterised by a strong vision and widespread impact. All participants hold a favourable opinion regarding the integration of entrepreneurship courses in the EFL classroom. This course align with the educational requirements of the 21st century. The entrepreneurial course positively influence the competence, skills, motivation, and mindset of respondents towards entrepreneurs, as well as enhance their English proficiency and skills. Nevertheless, certain limitations persist in the realm of entrepreneurial learning, including the execution of the online learner model, theoretical content, physical resources, and limited time periods for learning, all of which hinder its effectiveness.